2020
DOI: 10.18006/2020.8(5).535.543
|View full text |Cite
|
Sign up to set email alerts
|

GENETIC VARIABILITY IN F5 AND F6 GENERATIONS OF BREAD WHEAT (Triticum Aestivum L.) UNDER TIMELY AND LATE SOWN CONDITIONS

Abstract: The present study was conducted to assess the genetic variability in 238 F5 and F6 progenies derived from WH 711 / WH 542 cross for nineteen yield, its components and physiological traits. Analysis of variance showed significant differences among the genotypes for all the traits. The phenotypic coefficient of variation was found higher than their respective genotypic coefficient of variation for all the traits in both the generations indicating the least influence of the environment. Moderate to High PCV and G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
0
0
Order By: Relevance
“…This favourable changes in the crop may be attributed to improved growth and development of the crop with thiourea treatment action potentially targeting the meristematic activity of apical tissues with stimulatory effects on cell division which promotes growth in shoot length and cell number for improved leaf area (mainly by higher sulphur and nitrogen nutrition). Thiourea boosted net photosynthetic rates as well as total chlorophyll and starch concentrations in the leaves, resulting in maximum plant height and branches [12]. Singh and Singh also reported that application of thiourea @ 500 ppm at pre-flowering and pod initiation stages significantly increased plant height and branches than the control treatments [13].…”
Section: Growth Attributesmentioning
confidence: 90%
“…This favourable changes in the crop may be attributed to improved growth and development of the crop with thiourea treatment action potentially targeting the meristematic activity of apical tissues with stimulatory effects on cell division which promotes growth in shoot length and cell number for improved leaf area (mainly by higher sulphur and nitrogen nutrition). Thiourea boosted net photosynthetic rates as well as total chlorophyll and starch concentrations in the leaves, resulting in maximum plant height and branches [12]. Singh and Singh also reported that application of thiourea @ 500 ppm at pre-flowering and pod initiation stages significantly increased plant height and branches than the control treatments [13].…”
Section: Growth Attributesmentioning
confidence: 90%